Relayout Gudang Bahan Baku Box Kemasan untuk Menurunkan Waktu Proses Perpindahan ke Lantai Produksi - Zahzilla, Jelita Nur; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. WKU is a manufacturing company that produces various types of packaging boxes using both a custom-made production system and a make-to-stock approach for certain products such as safety boxes. The company’s operational activities rely heavily on the availability of raw materials, primarily corrugated board, kraft liner, duplex board, and white kraft. The raw material warehouse, which has dimensions of 65 × 63,5 meters, is currently not optimally arranged. Pallet spacing is too narrow, causing inefficiencies in material retrieval because workers must move other pallets to access materials located at the back. This study aims to design a more effective warehouse layout using the ABC classification method based on movement frequency and a dedicated storage system. Inbound and outbound movement data were analyzed to calculate the frequency of material movement, which was then classified using the Pareto principle to determine storage priority levels. The results show that Duplex Board, Corrugated Board Single Wall 6 mm, and Kraft Liner fall into Class A, indicating the highest movement frequency.